2007
DOI: 10.1152/ajplung.00081.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke irreversibly modifies glutathione in airway epithelial cells

Abstract: In patients with chronic obstructive pulmonary disease (COPD), an imbalance between oxidants and antioxidants is acknowledged to result in disease development and progression. Cigarette smoke (CS) is known to deplete total glutathione (GSH + GSSG) in the airways. We hypothesized that components in the gaseous phase of CS may irreversibly react with GSH to form GSH derivatives that cannot be reduced (GSX), thereby causing this depletion. To understand this phenomenon, we investigated the effect of CS on GSH met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
72
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 32 publications
9
72
1
1
Order By: Relevance
“…4,22,23) In addition, it has been reported that a substantial amount of GSH in epithelial cells exposed to the gaseous phase of cigarette smoke is irreversibly modified to the GSH-ACR adduct (m/z 364) and GSH-CA adduct (m/z 378) by direct infusion mass spectra of the cell lysate, but the GSH-MVK adduct (m/z 378) and GSH-CA adduct are not separated. 7) Furthermore, it has been reported that the GSH-ACR and GSH-CA adducts can be detected in airway epithelial cells exposed to cigarette smoke, although the rela- tive yields were limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,22,23) In addition, it has been reported that a substantial amount of GSH in epithelial cells exposed to the gaseous phase of cigarette smoke is irreversibly modified to the GSH-ACR adduct (m/z 364) and GSH-CA adduct (m/z 378) by direct infusion mass spectra of the cell lysate, but the GSH-MVK adduct (m/z 378) and GSH-CA adduct are not separated. 7) Furthermore, it has been reported that the GSH-ACR and GSH-CA adducts can be detected in airway epithelial cells exposed to cigarette smoke, although the rela- tive yields were limited.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Among them, the α,β-unsaturated aldehydes acrolein (ACR) and crotonaldehyde (CA), abundantly present in cigarette smoke, have been often reported to strongly react with protein and peptide thiol groups. [5][6][7][8][9][10] In particular, glutathione (GSH), a tripeptide containing a thiol group, is an important antioxidant and essential cofactor for antioxidant enzyme glutathione peroxidase. ACR and CA can chemically or enzymatically react with GSH to form their corresponding Michael adducts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] In contrast to ROS, carbonyl compounds, which are relatively stable, extremely hydrophilic, and chemically reactive, pass through the airway epithelial barrier, enter the systemic circulation, and increase systemic oxidative stress and oxidative damage, contributing to the development of chronic diseases such as atherosclerosis, diabetes, and chronic obstructive pulmonary disease (COPD). [15][16][17] In addition, carbonyl compounds can induce carbonylation of proteins, which is an irreversible oxidative damage often associated with loss of protein function and accumulation of damaged or unfolded proteins. 18) Cigarette smoke may induce endogenous ROS production via continuous activation of reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) in inflammatory cells including macrophages, neutrophils, and epithelial cells, leading to chronic inflammatory conditions such as COPD.…”
Section: Chemical Substances Identified In Tar and Gas Phases Of Cigamentioning
confidence: 99%
“…The gaseous phase of cigarette smoke contains many reactive oxidants such as superoxide anion, nitric oxides and peroxynitrites, as reviewed recently (MacNee b2005; Lin & Thomas 2010). Oxidants and free radicals inhaled in tobacco smoke, can damage airway epithelial cells, and impair antioxidants, such as glutathione to non-reducible glutathione-aldehyde derivatives (van Der Toorn et al, 2007). Oxidants from tobacco smoke may also inactivate antiproteases, predisposing to a protease-antiprotease imbalance from the increased numbers of neutrophils and macrophages in smokers' lungs.…”
Section: Role Of Oxidants In Protease-antiprotease Imbalancementioning
confidence: 99%